Perlindungan Hukum terhadap Konsumen yang Mengkonsumsi Daging Ayam Tidak Layak Jual di Pasar Badung – Bali - Adinikum Keba Tunggu; I Nyoman Putu Budiartha; Ni Made Sukariyati Karma (Jurnal Konstruksi Hukum, 2020)
Consumer protection is a legal instrument created to protect and fulfill the rights of consumers according to the correct procedures. However according to existing problems in the field resulting in losses for consumers. In this case business actors often commit fraud in order to obtain maximum profit or actions taken by business actors it is only in their interests to enrich themselves even though such actions are clearly violated by legislators. In law number 8 of 1999 concerning consumer protection in article 1 paragraph 2 consumers are every person using goods and / or services available in the community both for self family other people and other living things and not for trade. This study aims to find out 1. How is the legal protection for consumers who consume chicken meat not worth selling at Badung Market. 2. What is the effort made by the Food and Drug Supervisor (BPOM) when the sale of chicken meat is not suitable for consumption? To answer the above researchers then use Empirical Method by collecting interview data then it is processed and analyzed into works of faith. And researchers identify legal issues and answer. Other legal symptoms in the literature.